2016
DOI: 10.1039/c6ra03090d
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of elastic and optical properties on surface terminated groups in two-dimensional MXene monolayers: a first-principles study

Abstract: The low adsorption and reflectivity from infrared to ultraviolet rays account for the high transmittance of Ti3C2T2that has been experimentally observed, and it is predicted that Ti2CT2will have higher optical transmittance in this range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
149
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 256 publications
(169 citation statements)
references
References 42 publications
11
149
0
Order By: Relevance
“…It is shown that, in the range of infrared to ultraviolet light including visible light, the in-plane absorption coefficients are lower for the F and OH functionalized MXenes than the bare and O functionalized ones [50]. By analyzing the refractivity, it is concluded that F and OH functionalized Ti 2 C and Ti 3 C 2 should exhibit white color [50].…”
Section: Optical Propertiesmentioning
confidence: 99%
See 3 more Smart Citations
“…It is shown that, in the range of infrared to ultraviolet light including visible light, the in-plane absorption coefficients are lower for the F and OH functionalized MXenes than the bare and O functionalized ones [50]. By analyzing the refractivity, it is concluded that F and OH functionalized Ti 2 C and Ti 3 C 2 should exhibit white color [50].…”
Section: Optical Propertiesmentioning
confidence: 99%
“…In other theoretical studies, the optical properties of pristine and functionalized Ti 2 C and Ti 3 C 2 with F, OH, and O have been examined [50]. It is shown that, in the range of infrared to ultraviolet light including visible light, the in-plane absorption coefficients are lower for the F and OH functionalized MXenes than the bare and O functionalized ones [50].…”
Section: Optical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is expected that the host structures of cathode materials should be as stable as possible, which may help the cathode to maintain excellent cycling performance and safety. In the meantime, first principles computation methods have showed superiority in developing and optimizing new energy storage and conversion materials, and predictions of the material properties [Bai et al, 2016;Kistanov et al, 2016]. Recently, olivine-type LiMPO 4 (M = Fe, Mn, Co, and Ni) cathode materials have been proved to be one of the promising candidate class for lithium-ion batteries due to their low cost, large energy density, and particularly high thermal and electrochemical stabilities.…”
Section: Introductionmentioning
confidence: 99%